2007
DOI: 10.1186/1479-5876-5-15
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of Y-90 microsphere treatment in patients with primary and metastatic liver cancer: The tumor selectivity of the treatment as a function of tumor to liver flow ratio

Abstract: Journal of Translational Medicine AbstractBackground: Treatment records and follow-up data on 40 patients with primary and metastatic liver malignancies who underwent a single whole-liver treatment with Y-90 resin microspheres (SIR-Spheres ® Sirtex Medical, Lake Forest, IL) were retrospectively reviewed. The objective of the study was to evaluate the anatomic and physiologic determinants of radiation dose distribution, and the dose response of tumor and liver toxicity in patients with liver malignancies who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
98
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(104 citation statements)
references
References 25 publications
2
98
1
3
Order By: Relevance
“…Their results provide reasoning to the D NL threshold noted in other clinical studies of 70 Gy using GMS [44] and approximately 40-50 Gy using RMS [13,45]. It should be noted that although no toxicity was noted with absorbed doses of up to 100 Gy [46], the manufacturer of RMS recommends a D NL of 80 Gy, and a recent summary suggests a preferable D NL of 50 Gy [29]. Toxicity of either GMS or RMS is not only dependent on the dose volume factors, but also on the patient population, underlying liver disease, liver function and concurrent therapies [47].…”
Section: Differences Between Rms and Gmssupporting
confidence: 54%
“…Their results provide reasoning to the D NL threshold noted in other clinical studies of 70 Gy using GMS [44] and approximately 40-50 Gy using RMS [13,45]. It should be noted that although no toxicity was noted with absorbed doses of up to 100 Gy [46], the manufacturer of RMS recommends a D NL of 80 Gy, and a recent summary suggests a preferable D NL of 50 Gy [29]. Toxicity of either GMS or RMS is not only dependent on the dose volume factors, but also on the patient population, underlying liver disease, liver function and concurrent therapies [47].…”
Section: Differences Between Rms and Gmssupporting
confidence: 54%
“…This is particularly the case for liver metastasized breast cancer, of which response rates of over 90% are reported [61,62]. 90 Y-RE has been applied in patients with neuroendocrine liver metastases, too, albeit in small numbers [11,63]. Reported response rates were 100%, and it would therefore be worthwhile to further explore the use of 90 Y-RE for this indication.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that favorable T/N uptake ratios of 99m Tc-MAA are associated with improved post-treatment tumor response [7,8,9], whereas other studies contradict these findings and emphasize that assuming an equal intrahepatic distribution of 99m Tc-MAA and 90 Y-microspheres may not be justified. [10,11,12,13] Still, a consistent finding of these studies is a strong interindividual heterogeneity in T/N uptake ratio's, with a reported range of 0.…”
Section: Introductionmentioning
confidence: 59%
“…6-25.9. [7,8,9,11,12,14,15,16,17] Furthermore, a recent study assessing the radioactive microsphere biodistribution on post-treatment quantitative imaging following radioembolization, demonstrated that the T/N uptake ratio per tumor may also show marked variability within the same liver. Up to 60% of the patients had at least one tumor that received a concentration of radioactivity equal to or lower than the normal liver tissue (T/N #1).…”
Section: Introductionmentioning
confidence: 99%